Perancangan Interior Pusat Informasi dalam Wisata Edukasi Pertanian di Desa Karanglo, Klaten, Jawa Tengah - Angela Budihartono (Intra, 2017)
Indonesia is a worldwide recognized agrarian country which has an enormous potential in agriculture sector. Nevertheless, the increasing demand of Indonesian citizens for agricultural products is not followed by great enthusiasm in the respected sector in Indonesia. This, however, might endanger the sustainability of Indonesian agriculture and food self-sufficient. One of the nation-wide largest rice producer in Indonesia is Karanglo Village in Central Java Province.  In this village, a lot of endeavors have been conducted to increase the productivity of paddy planting and further, the sustainability of agriculture sector. Provision of the agriculture educational tourist site's information center  in Karanglo Village can be regarded as one of the most beneficial endeavor to educate and improve citizens' awareness towards agriculture sector in Indonesia. Nonetheless, this information center needs to be well-designed in terms of its interior parts since interior design can underpin and provide better approach on the site's guests.